Evaluation of the role of information and communication technologies in rural development using A'WOT analysis - Öztaş Karlı, Rukiye Gizem; Karlı, Rukiye Gizem Öztaş (Centenary University, 2021)
Globalization and developing technology have caused the concept of rural development to change. In this context, the use of information and communication technologies (ICT) in rural areas should increase in order to keep pace with the globalizing world, contribute to socio-economic development and create smart and competitive rural areas. Although A'WOT technique has been used in various fields in the literature, it has been observed that there is not enough work in rural development studies except tourism. This study aims to determine the role of ICTs in putting ICT in rural development is to evaluate the potential of rural areas in Turkey A'WOT analysis. In numerical analysis, the opinions of 9 experts were used as data. Findings show that although the infrastructure of rural areas is highly completed and smart agriculture applications are used, ICT device ownership and access opportunities are insufficient. The fact that the Internet of Things (IoT) technology can be used in every field is seen as an important opportunity, and it is an important threat that rural people show a distant stance against ICT in agricultural practices. © 2021 Elsevier B.V., All rights reserved.
Bilgi ve İletişim Teknolojilerinin Kırsal Kalkınmadaki Rolünün A'WOT Analizi ile Değerlendirilmesi
Keywords: A'wot Analysis; Ict; Rural Development; Smart Rural Area